Operation of the transistor as a low-level switch and its applications in analogue-to-digital converters - Verster, T. C.(Theunis Christiaan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Ing.) -- University of Stellenbosch, 1963.